Kayutangan Area's Road Network Performance Evaluation Post Implementation of Traffic Management Since 2023 - Susanto, Bagus; Djakfar, Ludfi; Wicaksono, Ahcmad (Rekayasa Sipil, 2025)
Kayutangan Heritage Village is making various kinds of improvements in the arrangement around the area. After the implementation of traffic management and engineering in the Kayutangan area by the Malang City Government, there were several changes in flow from the north and south sides of Malang City, where several road networks in the area used a one-way system and changed the characteristics of the roads. By using 2023 IRCG and assisted by the VISSIM 2020 application, conclusions can be drawn with the changes that have been implemented in this area, Brigjend Slamet Riadi road section has VCr 1,116, Basuki Rahmat St (segment 1) 1,080, Basuki Rahmat St (segment 2) 0,732, Kahuripan St 0,781, Semeru St 0,850, Basuki Rahmat St (segment 3) 0,930, Brawijaya St 0,596, Jalan Mojopahit 0,978, Jalan MGR Sugiyopranoto (segment 1) 0,916, Aries Munandar St 0,798, MGR Sugiyopranoto St (segment 2) 0,951, Merdeka Utara St 0,234,  and Merdeka Timur St 0.909 with average VCr after traffic management is implemented is 0,85 – 1,20 during peak hours. This indicates that there is a need for recommendations for further handling to improve road network services.